Peran Kepala Sekolah Dalam Mengembangkan Sekolah Adiwiyata Di SMAN 1 Babat Lamongan - Muhammad Nur Mahfudh; Muhammad Ainur Rafiq; Mustika Wulandari (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2022)
This research is the result of field research on the role of the principal in developing an adiwiyata school at SMAN 1 Babat Lamongan. The focus of this research is to review, 1) Describe the role of the principal in developing an adiwiyata school at SMAN 1 Babat Lamongan, 2) Describe the supporting and inhibiting factors in developing the adiwiyata program at SMAN 1 Babat Lamongan. In this study, the researcher used descriptive qualitative research data, namely research procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. The data sources that the researchers obtained came from primary and secondary data. Data collection techniques using observation, interviews, and documentation. Data analysis uses an interactive model through data reduction, data presentation, drawing conclusions. The technique of checking the validity of the data is through source triangulation, technical triangulation, and time triangulation. The results of the research conducted show the following conclusions: 1) The principal is very involved in developing the Adiwiyata school at SMAN 1 Babat Lamongan as an educator who is an example for educators, as a manager who controls and regulates appropriate results, as an administrator, as a supervisor, as leaders who improve the ability of educators in the development of adiwiyata, as innovators by seeking innovative new ideas and integrating each activity, and as motivators. 2) Factors supporting the development of the Adiwiyata program include: active participation of all school members in implementing the Adiwiyata program, adequate facilities and infrastructure, curriculum structure related to environmental protection and management policies, collaboration partners in environmental activities, special budget for activities adiwiyata, educators have competence in developing environmental learning activities.